The Impact of Halal Certification, Digital Payment Convenience, and Product Diversity on Purchasing Decisions: The Mediating Role of Purchase Interest (Study on Cassava Cheese Consumers in Argotelo Salatiga) - Dyah_23; Sarja (Journal of Islamic Enterpreneurship and Management, 2024)
This research is a quantitative descriptive study which aims to analyze the influence of halal certification, ease of digital payment, and product diversity on purchasing decisions with purchase intention as an intervening variable carried out on Argotelo Salatiga Cheese Cassava consumers. Using the Theory of Planned Behavior approach. The sample in this study consisted of 100 respondents who were taken using purposive sampling with the condition that they had consumed Argotelo Salatiga Cassava Cheese products. The data analysis technique uses the path analysis method and Sobel test. The research results show that halal certification and ease of digital payment have no influence on purchasing decisions, while product diversity has an influence on purchasing decisions. The purchasing interest variable is able to mediate between halal certification, ease of digital payment, and product diversity on purchasing decisions.